An Investigation of College Students' Information Literacy, Interaction, and Preferences in Online Learning during the COVID-19 Pandemic - Wang, Xuan; Yang, Harrison Hao; Zuo, Can; Shi, Yinghui; Tian, Jun; Wang, Daiqi (International Symposium on Educational Technology (Print), 2021)
College students are the online learning subjects in the Covid-19 pandemic and their preferences towards online learning have certain reference value for the subsequent improvement of online learning platforms and the optimization of online teaching and learning. The study combined information literacy with Uses and Gratifications Theory, characterized students' online learning preferences with usage, gratifications, and acceptance, and introduced online interaction to construct an influencing factor model for university students' preferences towards online learning. The partial least squares method was used to verify the measurement model and structural model. All the research hypotheses are supported by the empirical research.